Perlindungan Hukum Terhadap Konsumen Atas Produk Skincare Ilegal Di indonesia - Repi Anggraini; Nurhayani; Yusra; Hasyya Acika Zulfira; Shinta Ulfa (Jurnal Kajian Hukum Dan Kebijakan Publik | E-ISSN : 3031-8882, 2023)
The skincare industry has become an important part of the modern lifestyle, with consumers increasingly concerned about the health and appearance of their skin. However, behind this rapidly growing market, there are big challenges related to illegal skincare products that can harm consumers. One of the main problems faced by consumers in the case of illegal skincare products is the lack of adequate legal protection. Producers of illegal products are often not subject to strict regulations, making it difficult for consumers to obtain compensation or legal enforcement against these producers. Therefore, this research aims to highlight the importance of legal protection for consumers of illegal skincare products. We will discuss the role of consumer protection laws, cosmetic product regulations, and intellectual property rights in protecting consumers from illegal skincare products. The research uses normative legal methods. According to Soekanto & Mamudji (2003), normative legal research is legal research carried out by examining library materials and secondary data. In summary, stricter law enforcement against manufacturers and retailers of illegal skin care products in Indonesia will reduce the prevalence of illegal products on the market and increase consumer protection. This includes a variety of measures, such as active law enforcement, increased sanctions and fines, strengthened production and distribution controls, stricter regulations, and public education and awareness campaigns. The government's efforts to provide consumer protection start from the licensing process, and violations of cosmetics regulations will be subject to administrative sanctions and criminal penalties. Consumers have the right to skin care products that are safe, of high quality, according to the label, and have the right to clear and correct information regarding cosmetic products.